2017
DOI: 10.1007/s00442-017-3868-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of competition on induction of crassulacean acid metabolism in a facultative CAM plant

Abstract: Abiotic drivers of environmental stress have been found to induce CAM expression (nocturnal carboxylation) in facultative CAM species such as Mesembryanthemum crystallinum. The role played by biotic factors such as competition with non-CAM species in affecting CAM expression, however, remains largely understudied. This research investigated the effects of salt and water conditions on the competition between M. crystallinum and the C grass Bromus mollis with which it is found to coexist in California's coastal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Previous studies showed that high drought resistance accounted for the competitive advantage of a model facultative CAM species ( M. crystallinum ) over its co‐occurring grass species ( B. mollis ) found in California grasslands under global change scenarios (Yu et al. , b). This study investigated whether water stress and concurrent CO 2 enrichment—which are known to affect the interactions between C 3 and C 4 plants (Smith et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that high drought resistance accounted for the competitive advantage of a model facultative CAM species ( M. crystallinum ) over its co‐occurring grass species ( B. mollis ) found in California grasslands under global change scenarios (Yu et al. , b). This study investigated whether water stress and concurrent CO 2 enrichment—which are known to affect the interactions between C 3 and C 4 plants (Smith et al.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al. (, b) experimentally found that a model facultative CAM species ( Mesembryanthemum crystallinum ) had a competitive advantage over a co‐occurring grass ( Bromus mollis ) in California under global change scenarios of increased drought, soil salinity, and nitrogen deposition. An empirical evaluation of the response of constitutive CAM plants and their competitive relationships with other functional groups (i.e., C 4 plants) to CO 2 enrichment and changing climate, however, is still missing (Poorter and Navas ).…”
Section: Introductionmentioning
confidence: 99%
“…2d). In fact, B. mollis is not drought tolerant (Yu et al 2017b(Yu et al , 2017c) and appeared to be severely damaged by early extreme droughts, thus restricting the ability of B. mollis to recover and benefit from later rainfall events (Walter et al 2011). This Bmemory^of early droughts was not significant for M. crystallinum which as facultative CAM plants have higher plant water contents and are more drought (Lüttge 2004;Borland et al 2009;Yu et al 2017bYu et al , 2017c.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of CAM plants are engendering scientific interest, particularly in recent years, because of their ability to adapt to drought through photosynthetic plasticity which may allow them to increase their dominance in a future (drier and warmer) climate (Drennan and Nobel 2000;Lüttge 2004;Borland et al 2009;Yu et al 2017bYu et al , 2017c. This study investigates the response of a model facultative CAM species (Mesembryanthemum crystallinum, occasional crop species) and its competitive relationship with a C 3 grass (Bromus mollis) to changes in rainfall regime (i.e., intra-seasonal rainfall variability and rainfall seasonality).…”
Section: Introductionmentioning
confidence: 99%
“…These key global change drivers (i.e., altered water and nutrient conditions) have been found to greatly affect ecological processes such as interspecific interactions in ecosystems where C 3 and/or C 4 plants dominate (Niu, Liu, & Wan, ; Van der Waal et al., ). It remains unclear, however, how water and nutrient conditions affect plants with crassulacean acid metabolism (CAM) and their competitive relationship with other functional types (but see Yu & D'Odorico, , ; Yu, D'Odorico, Li, & He, ).…”
Section: Introductionmentioning
confidence: 99%